1998
DOI: 10.1080/15216549800202802
|View full text |Cite
|
Sign up to set email alerts
|

Captopril ameliorates myocardial and hematological toxicities induced by adriamycin

Abstract: Adriamycin has a wide spectrum of antitumor activity with dose related cardiotoxicity as a major side effect. The objective of this study was to investigate the influence of captopril, a sulphydryl containing angiotensin converting enzyme inhibitor, on the cardio‐and hematotoxicity of adriamycin in normal rats. A single dose of adriamycin (15 mg/kg) caused myocardial toxicity after 24 h manifested biochemically by elevation of serum enzymes:‐ Aspartate transaminase (AST, EC: 2.6.1.1), lactate dehydrogenase (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…For instance, any changes in ALT level compared with the control was found at the lowest dose of doxorubicin and additionally relative elevations of AST compared with the control were higher than ALT. These results are in agreement with previous studies by Al-Shabanah et al [3] and Buyukokuroglu et al [6] who exposed rats to doxorubicin (15 or 20 mg/kg) and observed significant increase in AST activity after 24 and 48 h, respectively. Yagmurca et al [29] revealed that AST activity remains elevated even 10 days after treatment with 20 mg of doxorubicin/kg.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For instance, any changes in ALT level compared with the control was found at the lowest dose of doxorubicin and additionally relative elevations of AST compared with the control were higher than ALT. These results are in agreement with previous studies by Al-Shabanah et al [3] and Buyukokuroglu et al [6] who exposed rats to doxorubicin (15 or 20 mg/kg) and observed significant increase in AST activity after 24 and 48 h, respectively. Yagmurca et al [29] revealed that AST activity remains elevated even 10 days after treatment with 20 mg of doxorubicin/kg.…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with the previously reported results which had shown an elevation in LDH activity in rats receiving single and repeated doses of doxorubicin [2,9,10]. Significant increase in total LDH activity and cardiac isoform activity was also described by Al-Shabanah et al [3] even at 3 h after treatment with 15 mg doxorubicin/kg, what implies that source of the enzyme can be cardiomyocytes. Effect of hypothyreosis on LDH changes caused by doxorubicin was seen in 4 cases -only at 96 h. InAn increase in LDH activity in group exposed exclusively to doxorubicin was not associated with CK changes, which abnormalities was notice occasionally in every tested period of time.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Captopril has been clearly shown to express immune regulating and anti-inflammatory properties. ACE inhibitors including captopril have proven to be beneficial in experimental autoimmune encephalomyelitis (Constantinescu et al, 1995), myocarditis (Godsel et al, 2003), adriamycin-induced myocardial and hematological toxicities (O. Al-Shabanah et al, 1998), Freund`s adjuvant arthritis (Agha and Mansour, 2000) and experimental rats` colitis (Jahovic et al, 2005). The ability of captopril to act as a reactive oxygene species (ROS) scavenger (Mira et al, 1993) was found to be of major importance in its protection against ischemia-reperfusion-induced arrhythmias (Birincioglu et al, 1997) and liver injury in rats (Gulluoglu et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical use of Dox has been seriously restricted because of the cardiotoxic side effects (Singal et al, 1987). Consequently, there is great interest in expanding the clinical usefulness of Dox by developing new agents in order to reduce its cardiotoxicity (Al-Shabanah et al, 1998a). Therefore, the administration of various agents with Dox has been reported.…”
Section: Introductionmentioning
confidence: 99%